Developing skills for employability with German Partners : 8 success stories from the Renewables and Cleantech Sector - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
This edition of the brochure "Developing Skills for Employability with German Partners" presents eight success stories of skill development in the renewable energies and environmental technology sector. It was realised in a joint effort by German and international partners. (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; Berufsbildung; Internationale Zusammenarbeit; Erneuerbare Energie; Umwelttechnik